The SOCIALIZATION AND IMPLEMENTATION OF SELF-DECLARE HALAL CERTIFICATION ASSISTANCE PROGRAM FOR MSE ACTIVITIES IN LAREN VILLAGE, BREBES TOWARDS INCREASING BUSINESS INCOME - Umi Chabibatus Zahro; Mukhroji; Mochamad Fathoni (Universitas Sahid Surakarta, 2023)
The article aims to describe the implementation of socialization and implementation of a mentoring program for halal certification through a self-declare scheme in Laren Village, Brebes. The method using participatory action research. The main finding of this study is that MSEs are encouraged to apply for independent halal certification due to religious factors and government incentives. The next finding is that there is a social transformation in the form of the use of appropriate technology for MSEs in applying for halal certification